Creating an integrated care model for childhood obesity: a randomized pilot study utilizing telehealth in a community primary care setting. Issue 6 (14th November 2016) - Fleischman, A.; Hourigan, S. E.; Lyon, H. N.; Landry, M. G.; Reynolds, J.; Steltz, S. K.; Robinson, L.; Keating, S.; Feldman, H. A.; Antonelli, R. C.; Ludwig, D. S.; Ebbeling, C. B.
Summary: In an integrated care model, involving primary care providers (PCPs) and obesity specialists, telehealth may be useful for overcoming barriers to treating childhood obesity. We conducted a pilot study comparing body mass index (BMI) changes between two arms (i) PCP in‐person clinic visits plus obesity specialist tele‐visits ( PCP visits + specialist tele‐visits ) and (ii) PCP in‐person clinic visits only ( PCP visits only ), with ongoing tele‐consultation between PCPs and obesity specialists for both arms. Patients ( N = 40, 10–17 years, BMI ≥ 95th percentile) were randomized to Group 1 or 2. Both groups had PCP visits every 3 months for 12 months. Using a cross‐over protocol, Group 1 had PCP visits + specialist tele‐visits during the first 6 months and PCP visits only during the second 6 months, and Group 2 followed the opposite sequence. Each of 12 tele‐visits was conducted by a dietitian or psychologist with a patient and parent. Retention rates were 90% at 6 months and 80% at 12 months. BMI ( z ‐score) decreased more for Group 1 (started with PCP visits + specialist tele‐visits) vs. Group 2 (started with PCP visits only) at 3 months (−0.11 vs. −0.05, P = 0.049) following frequent tele‐visits. At 6 months (primary outcome), BMI was lower than baseline within Group 1 (−0.11, P = 0.0006) but not Group 2 (−0.06, P = 0.08); however, decrease in BMI at 6 months did not differ between groups. After crossover, BMI remained lower than baseline for Group 1 and dropped below baseline for Group 2. An integrated care model utilizing telehealth holds promise for treating children with obesity.